The Protective Role of Vitamin E against Oxidative Stress and Immunosuppression Induced by Non-Esterified Fatty Acids in Bovine Peripheral Blood Leukocytes - Li, Cheng-Yan; Lin, Wei-Chen; Moonmanee, Tossapol; Chan, Jacky Peng-Wen; Wang, Chien-Kai (Animals (Basel), 2024)
High levels of non-esterified fatty acids (NEFAs) during the transition period lead to increased oxidative stress and immunosuppression in cows. Feeding them a vitamin-E-supplemented diet reduces reactive oxygen species (ROS) levels in the blood and diminishes immunosuppression in the transition period. However, whether the restoration of immune cell function occurs through the direct action of vitamin E in cells is still a topic that requires further discussion. Therefore, in this experiment, we aimed to investigate the effect of NEFAs on peripheral blood leukocytes (PBLs) and whether vitamin E mitigates the impact of NEFAs. We employed three groups: (1) blank, (2) NEFA only, and (3) pre-culturing with vitamin E before NEFA treatment (VENEFA). In peripheral blood mononuclear cells (PBMCs), there were no differences in vitamin E content among the three groups. However, in the vitamin E pre-treatment group, the vitamin E levels of polymorphonuclear neutrophils (PMNs) were significantly higher than those in the other two groups. NEFA levels increased malondialdehyde (MDA) levels in PBMCs, but pre-treatment with vitamin E reduced accumulation of MDA levels. Regarding the expression of proinflammatory genes, NEFAs increased the expression of interleukin-1β in PBMCs and colony-stimulating factor 2 in PMNs. Vitamin E pre-treatment restored the increase in interleukin-1β levels caused by NEFAs in PBMCs. None of the groups affected the phagocytosis of PMNs. Few studies have confirmed that NEFAs cause oxidative stress in bovine PBLs. In summary, this study found that NEFAs induce oxidative stress in PBLs and alter the expression of inflammation-related genes; meanwhile, vitamin E can reduce some of the effects caused by NEFAs. This result may suggest that vitamin E can assist bovine PBLs in resisting the immune suppression caused by an NEB during the transition period.